Importancia de las TIC en los procesos de enseñanza-aprendizaje: estudios en la educación media y superior. - Morales Pinero, Juan Carlos; Cote Sanchez, Maria Carolina; Molina Bernal, Irma Amalia; Rodríguez-Jerez, Sergio Alejandro (Universidad Sergio Arboleda, 2022)
El proceso de integración de las TIC en la educación ha sido un fenó-meno muy estudiado en las últimas décadas. Mas en los últimos cinco años, la preocupación por mejorar la educación a partir de las nuevas tecnologías se incrementa debido a las dinámicas propias de lo que aho-ra se denomina la era digital. Por tanto, el presente capítulo tiene como objetivo analizar las publicaciones más relevantes en torno a la temática referida para describir el statu estado del arte. Para tal fin, se utiliza como perspectiva de análisis el modelo TPACK debido a su alta rele-vancia en el estudio de la integración TIC con la educación. Asimismo, el método descriptivo utilizó, como herramienta de análisis hermenéu-tico, la técnica de niveles de interpretación propuesto por Rodríguez Je-rez (2019). Los resultados obtenidos son organizados a partir de la zona y las unidades de convergencia encontradas. Las conclusiones brindan un marco de reflexión para comprender el proceso actual de integración de las TIC en los procesos de enseñanza y aprendizaje.
ICT and its impact on academic results: an analysis based on the TPACK model
The incorporation of ICT in education has become an innovative technique for the improvement of teaching-learning processes. The objective of this study is to analyze the incidence of ICT in the results of the Saber 11 tests developed in 2016, in Cundinamarca and Bogota. Since the incorporation of ICT in the classroom should not be analyzed in isolation, we will take the TPACK model as a frame of reference for this study. This model integrates the two main components of education (pedagogy and content) and technology. A questionnaire was designed and applied to facilitate the collection of information on teachers' competencies in relation to the TPACK model. Likewise, a quantitative analysis (linear regression and ANOVA) was proposed, which took as independent variable the average of the results obtained by the students grouped by institution. This made it possible to observe the variations in their behavior in contrast with the different independent variables. From the results obtained, the relevance obtained by the students' socioeconomic family stratum (Sig. = 0.000) to explain the behavior of the independent variable and the negative relationship between the technological infrastructure and the results obtained in the standardized tests of the official schools stand out. In conclusion, the study corroborates previous research, establishing that institutions of higher socioeconomic status will obtain better results than those of lower socioeconomic status. However, the current integration of technology, pedagogy and content are not relevant inputs to explain the results of the Saber 11 tests.
Keywords: TIC; educación; modelo TPACK; education; saber 11 tests; socioeconomic level; sector; teacher; WOS(2)